IMPLEMENTASI LATIHAN ROM AKTIF UNTUK PENINGKATAN SENSITIVITAS KAKI PADA PASIEN DIABETES MELITUS TIPE II DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Karo, Hanna Melenia Karo; Arianti, Ika; Fentiana, Nina (SINERGI : Jurnal Riset Ilmiah, 2025)
In the era of globalization, there has been a shift from communicable to noncommunicable diseases, with an increasing prevalence of degenerative illnesses, one of which is diabetes mellitus. Prolonged high blood glucose levels in patients with diabetes mellitus can lead to various chronic complications. This study aims to examine the improvement offoot sensitivity in patients with Type Il Diabetes Mellitus at TK 11 Putri Hijau Hospital, Medan. This research employed a descriptive case study design by collecting data using observation sheets and random blood glucose checks. The subjects were two patients with impaired foot sensitivity due to Type 11 Diabetes Mellitus at TK 11 Putri Hijau Hospital. The results showed an improvement in foot sensitivity following regular active range of motion (ROM) exercises. It can be concluded that the implementation of active ROM exercises on the feet can enhance foot sensitivity in patients with Type 11 Diabetes Mellitus. It is recommended that patients with Type 11 Diabetes Mellitus perform active ROM exercises as frequently as possible as a non-pharmacological therapy to stabilize and improve foot sensitivity.